Semantic Domain of Being in Hamzah Fansuri’s “Sidang Fakir Empunya Kata” Poem - Ahsanuddin, Mohammad; ., Irhamni; Asrori, Imam (KnE Social Sciences, 2020)
Writing poetry is inseparable from the field of meaning contained in each word used by the author. Among the many types of meaning fields, ‘being’ is one of most often used by Hamzah Fansuri, a poet who is famous for his work in the Sufi field, where he often uses a mixture of Arabic and Indonesian. This study aims to describe the field of meaning of being in Master of the Words by Hamzah Fansuri. The research method used is descriptive qualitative. The results showed that the field of meaning in the category of being was a semantic category related to abstract human concepts or experiences. The distinctive feature of this category is the prediction exists, although it cannot be lived directly by the human senses. In the words of the Fakir Empower, VHamzah Fansuri uses a lot of words that are included in the category of being, where the words are related to abstract human concepts or experiences. As the word faqir,machbub, zahir, da’im, and so forth. Keywords: being, semantic domain, Hamzah Fansuri, poem.